A Study on Correlation of Umbilical Cord Arterial Blood pH with Perinatal Asphyxia & Early Neonatal Outcome - Nutan Singh; Asheesh Kumar Gupta; Ajay Kumar Arya (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Perinatal asphyxia is one of the major causes of neonatal morbidity & mortality. Asphyxia can damage almost every organ of neonate. Our purpose was to determine the correlation of cord blood pH with birth asphyxia & early neonatal outcome. Subjects and Methods: A prospective study was conducted over a period of one year at STH Haldwani. We enrolled 108 term neonates with signs of fetal distress, thick MSL, non-reassuring NST & there were subjected for estimation of umbilical cord blood pH, APGAR score, outcome looked were resuscitation needed, NICU admission, delay in feed & encephalopathy (sarnat & sarnat stage). Results: In our study, cord blood pH had significant correlation with perinatal asphyxia(R=-0.926). Area under ROC curved showed that mean pH <7.1 (ROC=0.998) is very significant in predicting the adverse outcome. Conclusion: Cord blood pH is very sensitive and specific & has good correlation in predicting the birth asphyxia & adverse neonatal outcome. Measurement of cord blood pH is recommended in all the neonates with signs of fetal distress.